Analisis Pengaruh Discount Rate, Cash Ratio, dan Selective Credit Control terhadap Perkembangan Aset Modal Ventura Syariah Periode 2017-2021 - Siti Mayang Sari; Muhammad Yafiz (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to determine the impact of the discount rate, cash ratio, and selective credit control simultaneously and each variable on the development of Islamic venture capital assets. This study uses an associative approach that asks the relationship between two or more variables. The research results confirm that; (1) The Discount Rate variable has no effect on the development of Islamic venture capital assets, as can be seen from the statistical results showing the value of α (0.136 <0.05) while the calculated value > t table (5.093 > 1.677). (2) The Cash Ratio variable has no effect on the development of Islamic venture capital assets, as can be seen from the statistical results showing the value of α (0.082 <0.05) while the value of t count > t table (2.952 > 1.677). (3) The Selective Credit Control variable has a significant influence on the development of Islamic venture capital assets, as seen from the statistical results showing the value of α (0.000 <0.05) while the calculated value > t table (3.546 > 1.677). (4) The results of the regression analysis found that the Discount Rate, Cash Ratio and Selective Credit Control variables simultaneously influence the development of Islamic venture capital assets by 93.9% while the remaining 6.1% is explained by other variables outside the estimation model.